Is the Perfluorinated Trityl Cation Worth a Revisit? A Theoretical Study on the Lewis Acidities and Stabilities of Highly Halogenated Trityl Derivatives. Issue 18 (6th May 2014) - Couchman, Shannon A.; Wilson, David J. D.; Dutton, Jason L.
Abstract: The relative Lewis acidities of a series of known, unknown and observed but unstable halogenated derivatives of the trityl cation have been probed in a computational study. The Lewis acidity was investigated from hydride, fluoride and methide affinities. The results indicate that the perhalogenated trityl cation [C(C6 F5 )3 ] + is a desirable synthetic target, especially in the modern age of weakly coordinating anions. Our results also indicate that the stable [C(C6 Cl5 )3 ] + cation may be an equally interesting Lewis acid. Abstract : A computational analysis of the hydride, methide and fluoride Lewis acidities of halogenated derivatives of the trityl cation is presented herein. DFT calculations suggest that this class of compounds is worthy of reexamination.